PRINCIPLES OF IMPLEMENTING LABOR DISCIPLINE IN ENTERPRISES IN UZBEKISTAN (International Scientific Journal Alfraganus, 2024)
It is known that labor discipline is an objective necessity in the production process. In the legalliterature, this concept has been interpreted in different ways. Labor discipline is a procedure that determines theinteraction of the participants in production, strengthened by legal norms. More simply, labor discipline refers to thenecessity of joint labor as well as the subordination of Labor participants to a certain order. Labor discipline is studiedas a subject of various disciplines. In the field of law, however, it is studied and researched as a legal category. labordiscipline is also important as an institution of labor law. This aspect of it is manifested as a system of legal norms thatregulate the rules of the internal Labor procedure of the enterprise, the duties of the employee and the employer, as wellas establishing honest labor and measures to stimulate it, and the disciplinary responsibility of employees for violationof labor discipline. labor discipline by its nature is also, to a certain extent, a mirror of the true behavior and moralityof the employee. Because, in this sense, it testifies to the production discipline of the employee and to what extent headheres to the established order in this regard. This article analyzes all the circumstances related to the labor disciplineof employees of enterprises and institutions through legal norms in Uzbekistan. Already, the state of labor productivityin production is largely directly related to whether employees adhere to labor discipline in the labor process or not.
Keywords: labor discipline, internal labor regulations, working conditions, Labor Code, encouragement, persuasion, disciplinary liability.